Enabling Leadership dan Organization Adaptability di Gereja Bethel Indonesia - Mazeba, Marwita Three; Saputra, Bobby Wiryawan (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
Religious organizations such as churches face increasing challenges in maintaining relevance amid rapid social, cultural, and technological changes. This study addresses the issue of how leadership can foster adaptability in a value-based community organization facing dual crisesnamely, the COVID-19 pandemic and a major earthquake. The research aims to examine the relationship between enabling leadership and organizational adaptability, with adaptive space as a mediating variable. Using a quantitative correlational method with a cross-sectional design, data were collected from 102 active ministry members at GBI Mamuju through validated Likert-scale questionnaires. Mediation analysis was conducted using PROCESS v4.2 in SPSS. The findings reveal that enabling leadership does not directly influence organizational adaptability; instead, this relationship is fully mediated by adaptive space. Dimensions such as head space, meetings, virtual and physical environments, and dynamics of conflicting and connecting play a critical role in integrating new ideas into the formal organizational structure. This study highlights that adaptive space serves not merely as a theoretical construct, but as a practical social mechanism that enables collaboration and innovation. The results suggest that investment in social infrastructure is essential for churches to support intergenerational leadership, encourage experimentation, and sustain meaningful transformation.